RATIO DECIDENDI PELAKU JUDI ONLINE SLOT (PADA PUTUSAN NOMOR 2283/PID.B/2021/PN.SBY) - Anisa Dwi Andiani; Ahmad Sholikhin Ruslie (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
One of the crimes that often occurs and worries the community is the crime of gambling. This crime arises because of the unstable condition of society both in terms of religion, economy, morals and legal awareness. With the advancement of technology, gambling has now moved into a marginally more affluent space. Advances in information and technology are in line with the number of internet users in Indonesia. Unfortunately, advances in information and technology are often used by some people to commit crimes in the digital world or cyber crimes. The ITE Law was formed to anticipate all forms of cyber crime involving the use of information technology, in accordance with the increasing intensity of digitalization, convergence and sustainable globalization of information technology, which has the potential to be misused to commit criminal acts. Finding the ratio decidendi of online slot gaming actors is the aim of this study. This study relies on primary and secondary material obtained through library research and employs a normative juridical methodology. Case Study of Decision Number 2283/Pid.B/2021/findings PN. Sby’s